A study on outcome of binding pancreaticogastrostomy following pancreaticoduodenectomy: A prospective observational study. (February 2018) - Routh, Dronacharya; Pathak, Nishant; Naidu, C.S.; Singh, A.K.; Rao, P.P.; Ranjan, Priya
Abstract: Introduction: The type of anastomosis of the pancreas following pancreaticoduodenectomy is often attributed to the reason for pancreatic leak. Results of various randomized trials comparing pancreaticojejunostomy and pancreaticogastrostomy are conflicting one suggesting advantage over the other and vice versa. In this study we intend to critically analyze a novel technique of binding pancreaticogastrostomy following pancreaticoduodenectomy. Aims and objectives: The aim of this study is to see the outcome of binding pancreaticogastrostomy by evaluating the technical aspects of binding PG and study the incidence of post-operative complications. Materials and methods: The study included all patients who had undergone binding pancreaticogastrostomy from Mar 2012 to Mar 2016 at a tertiary care hospital. Patients' data, including patients demographics, type of procedure performed, complications, mortality, hospital stay, postoperative interventional procedures or reoperations were all documented. Results: There were 60 men and 37 women (mean age was 55.4 ± 11.6 years) with a mean BMI of 22.6 Kg/M 2 . 16% of the patients had evidence of cholangitis and 14 of them had to be stented preoperatively. Ninety-four percent of the patients were operated for malignant cause of obstructive jaundice. The mean operative time was 283 min s and average blood loss during surgery was 352 ml. 36% of the patients were operated by the senior residents undergoing training in Gastro intestinal surgery with the assistance of the available faculty. 60% of the patients had a pancreatic duct diameter less than 3 mm. 72% of the pancreatic stump were soft in consistency. In our study we had 3% patients with pancreatic leak. The most frequent complication was DGE, which was seen in 22% patients. The mean duration of DGE was 13.5 ± 2.6 days. We had 2 deaths within 30 days of surgery of which one was due to massive intraabdominal bleed due to pancreatic leak. None of the parameters like pre-operative and operative parameters like age, bilirubin, total leucocyte count, preoperative stenting, pancreatic duct diameter, texture of pancreas and surgery performed by residents were found to be responsible for pancreatic leak. Conclusion: This novel method of binding PG is simple, secure, and reproducible. It possesses several advantages over the conventional PG: it is very easy to perform, it is less traumatic to the pancreatic stump, can be performed in all types of pancreatic stump irrespective of the texture and diameter of the pancreatic duct without any statistically significant adverse outcomes. Highlights: A novel method of binding pancreaticogastrostomy where a purse string suture is taken on the posterior wall of the stomach with additional 4 corner sutures. The technique is simple, secure, and reproducible and possesses several advantages over the conventional methods. It is very easy to perform, less traumatic to the pancreatic stump and can be performed in all types of pancreatic stump irrespective of the texture and diameter of the pancreatic duct without any statistically significant adverse outcomes.